The Case of Elaine W. v. Joint Diseases North General Hospital, Inc.: When Treating Women Equally Means Equal Access to Treatment - Taub, Nadine; Davidson, Sheryl Felecia; Evans, Wanda; Warden, Tamasine (Columbia Journal of Gender and Law, 1992)
In recent years, society has been much concerned with the problem of pregnant women who are substance users and abusers. Though the studies do not conclusively show the extent and nature of fetal harm attributable to drugs, it seems clear the prenatal use of illicit drugs can disturb the course of pregnancies and undermine the health of later-born children. Much of the response to the problem has taken a punitive form-prosecutions, heightened sentences, and attempts to terminate parental rights. At the same time, pregnant women who do seek help have found the doors of treatment programs closed in their faces. In 1989, three pregnant women brought a class action suit challenging the exclusionary practices of four substance abuse treatment programs in the New York City area. The suit led to several favorable settlements and a decision from the Appellate Division of the New York Supreme Court. The decision, Elaine W. v. Joint Diseases North General Hospital, Inc., states that general assertions, by doctors responsible for the treatment programs, that pregnant women cannot be treated consistent with sound medical policy suffice to justify the exclusion. What follows is the amicus brief submitted to the Appellate Division in the Elaine W. case by the American Public Health Association arguing that, consistent with New York State’s Human Rights Law, treatment programs cannot exclude pregnant women without demonstrating a bona fide consideration of public policy.